Hyperparathyroidism in Patients with End-Stage Chronic Liver Disease (Clinical Observations) - A. A. Lavreniuk; A. N. Gorbacheva; E. E. Bibik; A. K. Eremkina; I. N. Tikhonov; N. G. Mokrysheva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present disorders of mineral and bone metabolism in patients with chronic liver diseases through clinical observations.Key points. The liver plays an important role in mineral metabolism: metabolic activation of vitamin D, synthesis of vitamin D-binding protein and albumin, metabolism of parathyroid hormone, etc. However, data on the development of mineral metabolism disorders, particularly hyperparathyroidism, in this population are very limited. Bone diseases such as osteoporosis and osteomalacia are quite common in chronic liver disease, especially in cirrhosis and cholestatic diseases; however, the pathogenesis of these disorders and their relationship with mineral metabolism remain poorly understood. The article presents cases of severe primary hyperparathyroidism (PHPT) in patients with chronic liver disease. In one patient with a long history of viral hepatitis C and cirrhosis, PHPT manifested with severe bone complications, including multiple vertebral compression fractures and a subsequent femoral neck fracture. Imaging studies revealed lesions of all four parathyroid glands, and the removal of the largest lesion did not result in disease remission. In the second case described, PHPT was diagnosed in a patient with bone pain and osteoporosis following orthotopic liver transplantation for Budd — Chiari syndrome with cirrhosis. One year after the initial surgical treatment for PHPT, the patient experienced a recurrence of the disease, with confirmed multiglandular lesion.Conclusion. In patients with chronic liver diseases, disorders of mineral and bone metabolism remain a significant yet not fully understood problem. Further studies are needed to develop therapeutic approaches for this group of patients to prevent the onset of late, disabling complications.